Towards an Archaeological Index: Identification of the Spectral Regions of Stress Vegetation Due to Buried Archaeological Remains - Georgopoulos, Andreas; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2012)
This paper aims to introduce the spectral characteristics of a new Archaeological Index for supporting remote sensing applications in archaeological research. This index will be able to enhance crop marks, observed in satellite images, which are related to buried archaeological remains. For the aims of the research, ground spectral signatures were acquired from two agricultural areas of Cyprus (Alampra and Acheleia), specifically constructed in order to simulate buried archaeological remains. A complete phenological cycle of barley and wheat crops was recorded using the GER 1500 spectroradiometer with spectral range from 350 - 1050 nm (visible - near infrared spectrum). Correlation regression analysis and evaluation separability indices have shown that results are similar for both sites -regardless crop type. The spectral sensitivity, for enhancement crop marks, was detected at the red edge and near infrared spectrum (≈ 700 and ≈ 800 nm)
Keywords: Archaeology; Remote sensing; Plants